A Cross Sectional Study on Assessment of Falls in Community Dwelling Elderly of Assam - Rashmi Agarwalla; Anku Moni Saikia; Rambha Pathak; Farzana Islam; Madhur Borah; Mamta Parashar (Medsci Publications, 2016)
Context: The five giants of geriatric that has been identified are immobility, instability (falls), incontinence, intellectual impairment and iatrogenic. Among these, falls are found to be a major problem in the elderly, causing injuries, dependence, psychological difficulties, and social isolation. Aims: The present study was done to assess the prevalence of falls in elderly and the factors associated with it. Settings and Design: This cross sectional study was done from August 2013 to December 2013 in Boko- Bongaon Block, Kamrup District, Assam. Methodology: A total of 360 elderly meeting the inclusion criteria were included in the study. A total of 30 clusters were selected and 12 elderly were selected from each cluster. Statistical analysis: Data was analyzed using SPSS version 20. Results: Out of 360 elderly, 41.9% had at least one fall in the past one year. Among them, 14.7% had more than 2 falls in the past one year. On analyzing the association of various factors with falls as dependent variable, older age group, unsatisfactory housing condition, dependent IADL, depression, presence of a co morbid condition and malnutrition were found to have significant association. Conclusion: The present findings reveal that falls is not an uncommon problem in the elderly.